ACTIVITIES AND DEVELOPMENT OF MARKETING COMMUNICATION IN SALES OF INSURANCE PRODUCTS POST-COVID-19 PANDEMIC - Daniel Susilo; Jason Enroe Wijaya (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Each insurance provider's services offer various types of insurance for the community through many methods of marketing communication approaches. One of the most widely done marketing communication activities by insurance service providers is personal selling, which are implemented by involving insurance agents as salespeople and communicator between the company and prospective customers. In general, personal selling activities are done through direct face-to-face communication between insurance agents and prospective customers, but the Covid-19 pandemic affected the insurance marketing and sales activities, causing the activities to be held online through virtual face-to-face platforms. Through this research, researchers want to analyze the communication process that can be done by an insurance agent to prospective customers either through directly face-to-face communication or virtual face-to-face. Researchers use several theories and concepts which are, marketing communication, personal selling, and media richness theory to see the comparison of communication between directly face-to-face communication with virtual communication. Researchers will conduct in-depth interviews with 4 source persons who are insurance marketers from PT Asuransi Allianz Life Indonesia and members of Vision Corporation.